Design and Build Temperature and Humidity Control Equipment in IoT-Based Rice Storage - Windy, Windy Alfira; Buaton, Relita; Sihombing, Marto (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This research aims to design and build a temperature and humidity control device in an Internet of Things (IoT)-based rice storage bin using the Blynk platform, ESP8266 module, DHT22 sensor, buzzer, 2-channel relay, fan, and lamp. The quality of rice is greatly affected by the conditions of the storage environment, especially temperature and humidity. Therefore, a system is needed that is able to monitor and control these two parameters in real-time to maintain the quality of rice during storage. The system is designed to use a DHT22 sensor to detect temperature and humidity, and then the data is sent to a ESP8266 microcontroller. A 2-channel relay sets the fan and lights to adjust the temperature and humidity, while the buzzer serves as a warning alarm. In addition, the system is equipped with an automatic notification feature through the Blynk application that informs users if the temperature or humidity exceeds a predetermined limit.